VISUALIZATION OF LEARNING CALCULUS USING AUTOGRAPH5 AT BUDI DARMA UNIVERSITY - Melda Panjaitan; Siti Nurhabibah Hutagalung (Institute of Computer Science (IOCS), 2021)
In Autograph5 Research on the application of using quadratic equations and calculating the volume of rotating objects at Budi Darma University for calculus lecture material in the form of visualization can make it easier for students to understand the use of software and its application. The application is carried out in the Computer Laboratory with online Visualization. The success rate of teaching evaluation on material delivery is almost 90% in the form of completing steps, stages of using application features, answering several case studies given 1D, 2D and 3D views, in this case students, respond very well, participate and get involved, to generate independence, learning creativity and application of learning materials in daily life.